The Influence of a Realistic Mathematics Education Approach on Students' Mathematical Problem Solving Ability - Fitriana, Hanny; Waswa, Anne N. (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this research is to determine the effect of a realistic mathematics education approach on students' mathematical problem solving abilities. Methodology: The method used was a quasi-experiment with a post-test only research design. Sampling was carried out using the cluster random sampling technique. The research instrument given was a test with a description type of 5 questions. Data analysis using the t-test from both groups obtained a t value of 4.47 , while t table was at a significance level of 5% with degrees of freedom (dk) = 47.09, namely 1.68, so it can be said that t count > t table. Main Findings: the results of hypothesis testing using the